2022
DOI: 10.1002/jsde.12609
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles and essential oils with antiviral activity on packaging and surfaces: An overview of their selection and application

Abstract: Until recently, food packaging has been used as a barrier to unfavorable environmental and microbial conditions, but new technologies are arising aimed at upgrading the protective nature of these materials. Cases of bacterial and viral transmission through food and surfaces have shown the vulnerabilities of the food packaging distribution systems over the years, creating awareness about new methods to prevent the proliferation of pathogens. This has been highlighted by safety concerns due to the COVID‐19 pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 307 publications
0
2
0
Order By: Relevance
“…LAB are Gram-positive, microaerophilic, and non-sporulating microorganisms with health benefits for the host, especially regarding dermal health, by improving the regulation of the skin and mucosa immune system and by maintaining cutaneous homeostasis [ 30 ]. In addition, studies showed that species from the genera Bacillus , Enterococcus , Streptococcus, or yeasts such as Saccharomyces , could be used as probiotics with efficient wound healing properties [ 26 , 31 ].…”
Section: Types Of Probiotics In Wound Healingmentioning
confidence: 99%
“…LAB are Gram-positive, microaerophilic, and non-sporulating microorganisms with health benefits for the host, especially regarding dermal health, by improving the regulation of the skin and mucosa immune system and by maintaining cutaneous homeostasis [ 30 ]. In addition, studies showed that species from the genera Bacillus , Enterococcus , Streptococcus, or yeasts such as Saccharomyces , could be used as probiotics with efficient wound healing properties [ 26 , 31 ].…”
Section: Types Of Probiotics In Wound Healingmentioning
confidence: 99%
“…In order to prepare antiviral coatings or films, many compounds, which are effective against viruses, such as SARS-CoV-2, such as ZnO nanoparticles, Ag nanoparticles, essential oils, and plant extracts, may be used [94][95][96][97][98][99][100]. As an example, Mizielińska et al [94] developed an active coating based on nanoparticles of ZnO, geraniol, and carvacrol.…”
Section: The Antiviral Properties Of Active Food Packagingmentioning
confidence: 99%
“…Therefore, in the design and development of cosmetic products, evaluating stability is crucial to ensure the safety, quality, and efficacy of the product [114]. Stability studies are conducted to define a product's shelf-life and evaluate necessary adjustments in formula-tions, packaging materials, storage conditions, transportation, etc., to ensure health and meet consumer expectations [114][115][116]. The use of physicochemical formulation in surfactant-oil-water (SOW) systems is crucial to tailoring the stability of emulsions and suspensions [3,118].…”
Section: Characterization and Evaluation Of Cosmetic Products' Stabilitymentioning
confidence: 99%
“…Droplet size can be influenced by factors such as emulsifier concentration. Additionally, process variables like homogenization and pressure can be controlled to tailor the droplet size using high-energy emulsification methods (e.g., homogenizers, microfluidizers, colloidal mills) [116]. Low-energy emulsification methods allow to also attain nanoemulsions with droplet size values lower than 500 nm [3].…”
Section: Droplet Sizementioning
confidence: 99%
See 1 more Smart Citation